Immune Responses to Pseudomonas aeruginosa Biofilm Infections - Moser, Claus; Jensen, Peter Østrup; Thomsen, Kim; Kolpen, Mette; Rybtke, Morten; Lauland, Anne Sofie; Trøstrup, Hannah; Tolker-Nielsen, Tim (Frontiers in Immunology, 2021)
Pseudomonas aeruginosa is a key pathogen of chronic infections in the lungs of cystic fibrosis patients and in patients suffering from chronic wounds of diverse aetiology. In these infections the bacteria congregate in biofilms and cannot be eradicated by standard antibiotic treatment or host immune responses. The persistent biofilms induce a hyper inflammatory state that results in collateral damage of the adjacent host tissue. The host fails to eradicate the biofilm infection, resulting in hindered remodeling and healing. In the present review we describe our current understanding of innate and adaptive immune responses elicited by P. aeruginosa biofilms in cystic fibrosis lung infections and chronic wounds. This includes the mechanisms that are involved in the activation of the immune responses, as well as the effector functions, the antimicrobial components and the associated tissue destruction. The mechanisms by which the biofilms evade immune responses, and potential treatment targets of the immune response are also discussed.